Tibetan Pig-Derived Probiotic Lactobacillus amylovorus SLZX20-1 Improved Intestinal Function via Producing Enzymes and Regulating Intestinal Microflora - Shen, Jiakun; Zhang, Jie; Zhao, Ying; Lin, Zishen; Ji, Linbao; Ma, Xi (Frontiers in Nutrition, 2022)
The interaction between exogenous microorganisms and the host has received great attention, and finding new probiotics is always the way to improve the health of humans and animals. Lactobacillus amylovorus (L.amylovorus) is a kind of Lactobacillus that can efficiently utilize starch, as a food and feed additive, it has been widely used for mildew prevention and antibacterial, bacteriostasis and enzyme production. Herein, a strain of L.amylovorus was isolated from the feces of Tibetan weaned piglets, named L.amylovorus SLZX20-1. Physiological and biochemical experiments in vitro confirmed that it had a fast growth rate and could produce a variety of enzymes, including α -galactosidase, α-glucosidase, α-glucosidase, β-glucosidase and ferulic acid esterase. In addition, L.amylovorus SLZX20-1 exerted antibiotic effects on the growth of S.typhimurium SL1344, C.Rodentium DBS100, S.Pullorum CVCC1791, S.aureus CVCC1882, E.coli O157, E.coli K88, E.coli K99, and E.coli 987P, which are closely related to acid productivity such as lactic acid and acetic acid. In vitro co-culture, L.amylovorus SLZX20-1 has shown the strong adhesion ability to IPEC-J2 cells and activated IPEC-J2 cells with high expression of host defense peptides, such as NK-Lysin, PEP2C and PBD-1. In vivo experiment, via intragastric administration, L.amylovorus SLZX20-1 significantly improved the feed intake of mice, declined the crypt depth of jejunum and ileum, L.amylovorus SLZX20-1 changed the composition of intestinal microbes to some extent, especially at the level of colonic genus, the dominant genus was changed from Lactobacillus to S24-7, which indicated the change of intestinal carbohydrate nutrition. In conclusion, L.amylovorus SLZX20-1 showed strong probiotic characteristics, which met with the standard of probiotics and is worth further exploring its impacts on host health and its potential as a candidate strain of probiotics.